Analysis of DNA instability in patients with periodontitis - R Swarnalakshmi; R Ramya; B Sabitha; Bharanidharan; A E Nagarathinam; K Raj Kumar (Wolters Kluwer Medknow Publications, 2017)
Introduction: Periodontitis is characterized by loss of supporting connective tissue and alveolar bone around teeth. Although triggered by bacterial infection other factors such as apoptosis and immune mediators such as interleukin - 1 (IL-1), tumor necrosis factor alpha, IL-6, and receptor activator of NF-κB ligand have found to aggravate the periodontal disease prognosis. Apoptosis is believed to contribute to periodontal disease progression. Cleavage of chromosomal DNA into oligonucleosomal size fragments is an integral part of apoptosis. DNA fragmentation factor. (DFF) is a major apoptotic endonuclease representative of DNA fragmentation. DFF is responsible for DNA fragmentation, a hallmark event during apoptosis. Aim: This study aims to determine the presence of DNA instability in tissue samples of chronic periodontitis using double-stranded DNA marker using immunohistochemistry. Methodology: Tissue samples of five chronic periodontitis cases and one control case was obtained. Patients of any age and sex with clinically and histologically diagnosed cases of chronic periodontitis were selected. The tissue samples were subjected to immunohistochemical analysis using DFF. Results: Staining index of DFF 45 was calculated by multiplying staining intensity and the staining percentage. Two cases showed positive expression with staining index moderate in one case and low in one case. Three cases did not express DFF. Conclusion: Apoptosis plays a critical role in the regulation of inflammation and host immune response. Mild to moderate degree of DNA instability is found to be present in chronic periodontitis patients. The presence of DNA instability in chronic periodontitis emphasizes the importance of devising effective treatment modalities.